Field characteristics and geochemistry of pyroxenite and gabbro from Odhimalai and Thenkalmalai hillocks of Bhavani ultramafic complex- South India - Karthikeyan, D. Prabhu, *K. Anbarasu, Ali Mohammed Dar, A. (International Multidisciplinary Research Journal, 2011)
The present study includes documentation of detailed geological field characteristics, petrography and geochemistry of mafic and ultramafic rocks associated with Odhimalai and Thenkalmalai hills of Bhavani complex. The lithologies well exposed in these two hillocks including Dunite, Pyroxenite, Gabbro, displaying layered arrangement comprising (from basement upwards) dunite, peridotite, pyroxenite and anorthosite-gabbro. The geochemical signatures of the gabbro and pyroxenites show a significant variation in major and trace element concentration. The pyroxenites show SiO2 composition ranging from 49.6-55.5%, Al2O3 from 6-13.6%, MgO from 3.6-14.3%, CaO from 8.4-15.5% and TiO2 from 0.24-1.7% while average composition of SiO2, Al2O3, MgO, CaO and TiO2 in gabbro varies (in %) from 49.9-58, 9.4-13, 7.4-13.1, 9-13.4 and 0.26-0.54 respectively. Ã‚Â